Targeting Endolysosomal Two-Pore Channels to Treat Cardiovascular Disorders in the Novel COronaVIrus Disease 2019 - Moccia, Francesco; Negri, Sharon; Faris, Pawan; Perna, Angelica; De Luca, Antonio; Soda, Teresa; Berra-Romani, Roberto; Guerra, Germano (Frontiers in Physiology, 2021)
Emerging evidence hints in favor of a life-threatening link between severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) and the cardiovascular system. SARS-CoV-2 may result in dramatic cardiovascular complications, whereas the severity of COronaVIrus Disease 2019 (COVID-19) and the incidence of fatalities tend to increase in patients with pre-existing cardiovascular complications. SARS-CoV-2 is internalized into the host cells by endocytosis and may then escape the endolysosomal system via endosomes. Two-pore channels drive endolysosomal trafficking through the release of endolysosomal Ca2+. Recent evidence suggested that the pharmacological inhibition of TPCs prevents Ebola virus and Middle East Respiratory Syndrome COronaVirus (MERS-CoV) entry into host cells. In this perspective, we briefly summarize the biophysical and pharmacological features of TPCs, illustrate their emerging role in the cardiovascular system, and finally present them as a reliable target to treat cardiovascular complications in COVID-19 patients.